The TLP 2-DOF as an alternative model for extreme wave application - Akmal, Jamiatul; Lubis, Asnawi; Tanti, Novri; Nuryanto, Nuryanto; Murti, Adam Wisnu (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2021)
Tension Leg Platform (TLP) is an offshore platform structure used for deep-sea oil and gas exploration. The main structure of the TLP consists of a deck, pontoon, mooring system, and foundation. TLP operates in a balance of buoyancy, structural weight, and mooring tension. The problem is the construction of TLP in the deep sea, where sometimes extreme waves appear could damage the TLP structure. This paper proposes a new model of TLP that is more stable to extreme waves. The method is to separate the mass of the deck and the mass of the pontoon into two flexible parts, which are connected by a cantilever spring system. Thus the TLP motion becomes two degrees of freedom (TLP 2-DOF). Using the dynamic vibration absorber (DVA) method, the ratio of the deck mass, pontoon mass, and spring stiffness are adjusted so that the primary mass movement is minimal. Furthermore, the ratio of the amplitude of the deck movement as the primary mass to the wave amplitude is analyzed, which is known as the operator response amplitude (RAO). The results showed that the TLP 2-DOF model was more stable. As an illustration, at resonance conditions, this model can reduce RAO to about 67%.